Informational and educational internet application, as a form of pharmaceutical intervention in the medication-taking behavior of the applicants of higher medical education - Zaremba, N; Zimenkovskyі, A (Annals of Mechnikov's Institute, 2019)
Aim: to work out the informational and educational model of pharmaceutical intervention in the medication-taking behavior of the applicants of higher medical education on the basis of modern information technologies to prevent the negative influence of self-medication on their state of health and quality of life. Materials and Methods. We have worked out the model of the educational and informative Internet application "Drug Compatibility Test" in the course of working out a new form of pharmaceutical intervention for the applicants of higher medical education regarding the interaction of drugs between themselves. There are used only free publicly available technologies and resources, while developing the Program of "Drug Compatibility Test", namely: Java programming languages (as part of Android Studio 3.2) and VB.NET (as part of Microsoft Visual Studio 2017 Community Edition – free software for individual developers and teams up to 6 participants), markup language of XML (as part of Android Studio 3.2), own graphic design (Paint.NET graphic editor – free software and programmatic graphics generation) and free, on conditions of attribution (placement of the reference to the source in the program), library of sound effects from the site www.zapsplat.com. The base of medicines, which are included in this Program, is formed on the basis of the results of the sociological survey on medication-taking behavior of the applicants of higher medical education. This database is formed on the basis of official instructions for medical use of drugs registered in Ukraine dated from October 28, 2018. Results. We have developed the Program of "Drug Compatibility Test" in the course of the study, it is the complete information application of mobile device, aimed at testing knowledge about the compatibility of medicines and certain aspects of the diet and behavioral habits of the user. Conclusions. 1. The program covers about 84 % of all mobile devices, in particular 98 % of mobile devices of ecosystem of Android 2. The program is free of charge and free for distribution under any conditions. 3. Base of medicines, which is included in the Program, formed on the basis of the results of our previous sociological survey about the most used drugs by the applicants of the higher medical education. If necessary, the base can be supplemented.